Design of Feed Rate Control System on Loss in Weight Feeder using Programmable Logic Controller - Wardhana, Asepta Surya; Nurin Hamdani, Chalidia; Kusuma Dewi, Astrie; Ravy, Javier Umar; Aji, Ferro; Hendrawati, Dwiana (Jurnal Polimesin, 2023)
In the industrial world where there is a material process or solid product, it definitely requires a consistent material distribution process to be used in the next process. And to move material from the main storage area, it is necessary to use a tool commonly called a feeder machine or Loss In Weight Feeder. This tool has a feeder system consisting of a hopper and a feeder mounted on a load cell with high accuracy. So in this study, a feed rate control system was designed on the Loss In Weight Feeder to keep the feed rate process at the desired value, so there is a controller to regulate the motor speed in the feeder. To run the control system, a parameter control is needed, namely PID. In this study, in designing the PID controller using Direct Synthesis tuning which will be carried out using two methods in producing a plant model, namely the process model, the proportional gain (Kp) value is 38.7, integral gain (Ki) is 0.6, and derivative gain (Kp) is 0.6. Kd) of 8.12. And the plant structure model of the Auto Regressive eXogenous (ARX) model, the proportional gain (Kp) value is 13, the integral gain (Ki) is 0.78, and the derivative gain (Kd) is 12.85. Based on direct testing, the PID controller parameter that is suitable and reliable with the desired process response from the feed rate output from the Loss In Weight Feeder prototype is the PID controller parameter using Direct Synthesis tuning based on the plant process model. In the system test without disturbance, it produces a time constant (τ) of 3 seconds, settling time (ts) of 5 seconds, delay time (td) of 1.5 seconds, overshoot (Mp) of 79.92% and steady state error (ess) of 0%. And when testing the prototype by providing interference, it shows a fairly good interference rejection